Developing Interactive Storytelling Model to Facilitate Young Learners’ Speaking Skills - Nurzaman, Istikhoroh; Gandana, Gilar; Wahidah, Annisa Shofaril (International Conference on Elementary Education, 2020)
Story-telling is a method that teachers can use in learning activities to facilitate young learners‟ development, especially their language development. Through story-telling, students are given opportunities to ask questions and provide responses in simple yet effective sentences. As Istikhoroh, Gilar, and Tri (2018) found, interactive story-telling program has positive effects on speaking skills improvement of 5- to 6-year-old learners. However, teachers‟ ability to perform story-telling activities still depends on fairy-tales or story books and hand puppets provided by the school. In other words, the instruction process tends to be conventional. Meanwhile, in this digital age, there are various technology-based facilities available, such as android application, which can be used in learning process to create an interactive learning atmosphere. Thus, the researcher conducted a further study to develop an android-based interactive story-telling model. The study aimed to describe the basic requirements of an android-based interactive story-telling model, the field test process of the model, and the reflection on the android-based interactive story-telling model. This study employed Reeves‟ Design Based Research (DBR) method. Data was gathered through interviews, field observation, audio and visual recording, and expert judgement techniques. The research instrument was internally validated by experts in early-childhood education and experts in language/linguistics. It also underwent an external validation through field testing in TK Perwari I, Tasikmalaya City; conducted in two separate time. In general, android-based interactive story-telling model is suitable for learning. The reflection on the development of this product yielded an android application-based interactive story-telling model to improve speaking skills in young learners